THE RELATIONSHIP BETWEEN MOTIVATION AND PERFECTIONISM TOWARDS SCHOLARSHIP RECIPIENTS (A STUDY ON STUDENT CREATIVITY PROGRAMS IN ESA UNGGUL UNIVERSITY) - Mariyanti, Sulis; Suarsi, Ika; Ratnaningtyas, Aisyah; Mariana, Citra (International Journal of Psychosocial Rehabilitation, 2020)
Scholarship for college students were demanded to finish PKM based on schedule, perfectly and following Dikti terms. By doing it, some of them did PKM based on criteria while some of them did not do it perfectly. In case to do it, college students need perfectionism into it. one of the factors that correlates with perfectionism is achievement motivation. This research aims to find the correlation between achievement motivation and perfectionism. The method of this research uses quantity study and correlational with incident al sampling with 137 samples. Achievement motivation scale is based on Mc.Celland theory with 21 valid items with (α) = 0.888 and perfectionism using Multidimential Perfectionism Scale by Frost with (α) = 0.930. Result of Pearson Product Moment showed that there is a correlation between achievement motivation with perfectionism coefficient correlation r = 0.253 with significant sig. 0.003 (p <0.05) it means this hypothesis accepted there is a positive correlation between achievement motivation with perfectionism. Beside that also found there is no gender correlation, GPA and parents education with achievement motivation while only parents education has correlation with perfectionism.